India Wins Freedom: The Complete Version - Maulana Abul Kalam Azad; AZAD (Maulana Abul Kalam) (Hyderabad Orient Longman Limited, 1988)
One of the makers of modern India tells the story of the partition of India as never before, with intimate knowledge and feeling. India Wins Freedom has at last won its own freedom. The full text of this autobiographical narrative was confined, under seal, in the National Library, Calcutta, and in the National Archives, New Delhi, for thirty years. What we now have is the complete text, released in September 1988, by a court directive. Not only have all the words and phrases of the original been reproduced, the original tone and temper have been fully restored. The text now reveals that the controversy that has simmered for so long about the hitherto unpublished pages, was fully justified.
Keywords: India -- Politics and government -- 1919-1947; India 1858-1947